2021
DOI: 10.3390/ijerph18137202
|View full text |Cite
|
Sign up to set email alerts
|

Fall-Related Activity Avoidance among Persons with Late Effects of Polio and Its Influence on Daily Life: A Mixed-Methods Study

Abstract: Falls are common among persons with late effects of polio (LEoP), which may lead to fear of falling and activity avoidance in everyday life. Here, we assessed the occurrence of fall-related activity avoidance among persons with LEoP and explored how these experiences influenced daily life. Fourteen ambulatory persons (seven women; mean age 70 years) with LEoP participated. They responded to the modified Survey of Activities and Fear of Falling in the Elderly (mSAFFE) and participated in individual interviews, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Additionally, not being able to manage certain activities, for example walk in the forest or participate in social events if there were stairs in the buildings, sometimes meant that they gave up meaningful activities. It has been reported that persons with LEoP [27], but also persons with PD [28], often avoid activities related to walking, such as going out when it is slippery, walking longer distances, and attending social events because of the fear of falling. Even if it can sometimes be beneficial to avoid activities that pose a high risk of falling, it may be emotionally difficult and frustrating not being able to perform meaningful activities anymore [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, not being able to manage certain activities, for example walk in the forest or participate in social events if there were stairs in the buildings, sometimes meant that they gave up meaningful activities. It has been reported that persons with LEoP [27], but also persons with PD [28], often avoid activities related to walking, such as going out when it is slippery, walking longer distances, and attending social events because of the fear of falling. Even if it can sometimes be beneficial to avoid activities that pose a high risk of falling, it may be emotionally difficult and frustrating not being able to perform meaningful activities anymore [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…FoF is defined as “an ongoing concern about falling that ultimately limits the performance of activities of daily living.” 15 It is described that up to 95% of persons with LEoP experience FoF when performing daily activities, 1,2,8,13,14 and for some, the fear is constantly in their mind 12 . FoF can lead to difficulties in carrying out household activities, leisure activities, participating in social events, 12 limiting physical activity, 16,17 and avoiding performing meaningful daily activities 18 . Therefore, it is of great importance to accurately assess FoF among persons with LEoP.…”
Section: Introductionmentioning
confidence: 99%
“…12 FoF can lead to difficulties in carrying out household activities, leisure activities, participating in social events, 12 limiting physical activity, 16,17 and avoiding performing meaningful daily activities. 18 Therefore, it is of great importance to accurately assess FoF among persons with LEoP.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have pointed out that, after the first fall, older persons tended to avoid activities that required them to be on their feet or walk, including showering, carrying out small household chores, walking in the external area of the house, and attending social events because of the injuries, pain, and fear of falling again [ 8 ]. Institutionalized older persons with cognitive decline were subject to the risk of having restrictions to mobility and activity imposed on them by their caretakers after the first fall episode, which promoted dependence and isolation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gait and balance alterations have been seen by caretakers as worrying risk factors that required special attention even in older persons without cognitive decline, which increased the chances of older persons having their mobility limited in nursing homes, especially in their external areas [ 5 , 9 , 10 , 11 ]. This impacted care delivery to this public [ 5 ] and caused caretakers to act in the place of older persons in many activities, which led to greater support in the execution of activities of daily living, dependence, gait ability loss, and muscle strength loss [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%